2001
DOI: 10.1103/physrevlett.87.196105
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Isotherms of Hydrogen: The Role of Thermal Fluctuations

Abstract: It is shown that experimentally obtained isotherms of adsorption on solid substrates may be completely reconciled with Lifshitz theory when thermal fluctuations are taken into account. This is achieved within the framework of a solid-on-solid model which is solved numerically. Analysis of the fluctuation contributions observed for hydrogen adsorption onto gold substrates allows to determine the surface tension of the free hydrogen film as a function of film thickness. It is found to decrease sharply for film t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…From a theoretical point of view, the influence of capillary fluctuations on wetting phenomena has attracted much attention as it could lead to nonuniversal wetting behavior with critical exponents depending explicitly on temperature [7,8]. Experimentally, the observation of this entropic repulsion in typical liquid layers is challenging, but some observations have shown that a correct description of adsorption isotherms of molecularly thin films could be achieved if one takes the entropic interaction into account [9][10][11][12].Similarly to simple liquids, mixtures of colloidal particles with nonadsorbing polymer can phase separate into a dense colloidal fluid phase (colloidal liquid) and a dilute one (colloidal gas) [13]. This phase separation is due to the depletion attraction that the polymer mediates between the colloids [14 -16].…”
mentioning
confidence: 99%
“…From a theoretical point of view, the influence of capillary fluctuations on wetting phenomena has attracted much attention as it could lead to nonuniversal wetting behavior with critical exponents depending explicitly on temperature [7,8]. Experimentally, the observation of this entropic repulsion in typical liquid layers is challenging, but some observations have shown that a correct description of adsorption isotherms of molecularly thin films could be achieved if one takes the entropic interaction into account [9][10][11][12].Similarly to simple liquids, mixtures of colloidal particles with nonadsorbing polymer can phase separate into a dense colloidal fluid phase (colloidal liquid) and a dilute one (colloidal gas) [13]. This phase separation is due to the depletion attraction that the polymer mediates between the colloids [14 -16].…”
mentioning
confidence: 99%
“…Especially regarding the thermal fluctuations this in contrast to published work. 10 Furthermore, the analysis of our experimental data suggests a Hamaker constant C 3 ≈ 6000 K Å 3 for molecular hydrogen on gold, based on the best fit at 14 K. (One has to note that, as in most other experiments with hydrogen, our substrates were not prepared under UHV conditions, hence there might be a contribution from a thin adsorbed water layer.) However, the measurement uncertainties allow for C 3 = 6000 …”
Section: Discussionmentioning
confidence: 77%
“…These may for example be related to the surface roughness of the substrate 8 and thermal fluctuations. 9,10 On the other hand, we have recently presented 11 experimental data using surface plasmon spectroscopy as a probe exhibiting a temperature dependence which cannot be understood by application of these theories. As we show below, however, the observed discrepancy is mainly due to the measurement method, and can be resolved, when the contribution of gas atoms to the surface plasmon signal is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…To do the mapping we employ a technique from Ref. [18] which proofed to work well for two dimensional membranes and thin films [19]. It considers the root mean square fluctuations amplitude σ 2 x,y = f 2 x,y given by σ −2 = 2 3/2 βκ 1/4 E 3/4 for parabolic confinement.…”
Section: ∂ R ∂Smentioning
confidence: 99%